The Role of Educational Leadership in Institutions: A Literature-Based Conceptual Framework of Concepts, Patterns and Determinants of Effectiveness - Nur Isra' Ahmad; Andi Takdir (International Journal of Education Management and Religion, 2026)
This study aims to develop a comprehensive understanding of educational leadership by examining its concepts, patterns, functions, and determinants of effectiveness through a literature-based approach. The research applies a qualitative descriptive design using library research and content analysis of academic sources published in reputable journals and scholarly works. The findings indicate that effective educational leadership is reflected in the integration of democratic and visionary patterns that support participation, collaboration, and strategic adaptability in responding to global challenges. Leadership effectiveness is shaped by interconnected factors, including regulatory frameworks, socio-economic conditions, institutional characteristics, leadership personality, professional qualifications, and organizational support. This study introduces a novel integrative conceptual framework that synthesizes these dimensions into a unified model and positions educational leadership as a multidimensional driver of institutional effectiveness. The framework also emphasizes its role in character formation, organizational performance, and global competitiveness. This research contributes to strengthening the theoretical foundation of educational leadership and provides a conceptual reference for future empirical studies and leadership development practices.